PENGARUH PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING TERHADAP KECERDASAN SOSIO-EMOSIONAL SISWA KELAS V SDN LIDAH KULON I SURABAYA - JATI PRATIWI, DIYANTI (PGSD FIP UNESA, 2015)
Abstrak Permasalahan yang muncul di dunia pendidikan dewasa ini adalah kurangnya implementasi hasil belajar siswa di lingkungan masyarakat. Hal ini dikarenakan sekolah hanya mengutamakan kecerdasan kognitif. Oleh sebab itu kecerdasan sosio-emosional dibutuhkan agar siswa mamu berperan dalam lingkungan sosialnya. Tujuan dari penelitian ini adalah untuk mngetahui signifikansi pengaruh model pembelajaran role playing terhadap kecerdasan sosio-emosional siswa kelas V SDN Lidah Kulon I Surabaya, dengan jumlah responden kelas eksperimen 31 siswa dan 33 siswa untuk kelas kontrol.Pengumpulan data dilakukan dengan observasi. Data yang didapat dianalisis dengan teknik t-test (uji-t). Nilai t hitung yang diambil adalah -7,209 untuk varians yang diasumsikan sama. Karena nilai probabilitas atau signifikansi t hitung berada di bawah 0,05 maka H0 ditolak. Dengan demikian terdapat perbedaan yang signifikan antara skor observasi kecerdasan sosioemosional siswa kelas eksperimen dengan kelas kontrol. Kata Kunci :model pembelajaran role playing, kecerdasan, sosio-emosional   Abstract Now days education have a whole meaning if we compare with ten and fifth teen years ago. Education’s successness  not only measured by cognitive intelligent, between cognitive and socio-emotional intelligent should be balance in order students can socialize and life in the society. Think how important socio emotional is, education role model which use to increase socio-emotional that is role playing education’s model. So, this research has purpose to know what is the significant effect to the fifth grade student’s socio-emotional in Lidah Wetan I Primary school through role playing model.. The method that used on this research is quantitative. Quasi  experiment is the kind of this research  with nonequivalent control group design. Located in Lidah Kulon I Primary School in 2015/2016. This research also use simple random sampling because the sample member are taken in random way. Sample in this research is V-A 33 student as a control class, and 31 student of V-c as an experiment class. Observation are used as a data collecting technique.The result of this research show us that there is a significant  effect in the socio-emotional observation research by using role playing model than conventional model. The value of t-test is -7,209 for a same varians. And signifikansi of t skor under the 0,05 so H0 is refused. So there is significant differences between experiments and control group for socio-emosional group.